1986
DOI: 10.1577/1548-8659(1986)115<485:gamfip>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Geosmin and Musty-Muddy Flavors in Pond-Raised Channel Catfish

Abstract: Monthly sensory (taste) analyses of channel catfish Ictalurus punctatus from 11 commercial culture ponds in Alabama during April‐October 1983 showed that earthy‐musty flavor was the major off‐flavor during the summer growing season. Geosmin (1,10‐trans‐dimethyl‐trans‐(9)‐decalol) was found by gas chromatography in detectable amounts, 3.7 to over 200 μg/kg of fish flesh, in 80% of fish having earthy‐musty or detritus (pond mud) flavor. Geosmin was not found in fish without these flavors. The geosmin analysis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 10 publications
1
32
1
1
Order By: Relevance
“…The uptake by fish occurs mainly through the gills or skin and leads to an earthy and musty smell and taste. A number of commercial important species such as Atlantic salmon, Salmo salar (Farmer et al, 1995), rainbow trout, Salmo gairdneri (From and Horlyck, 1984), catfish species (Lovell et al, 1986;Martin et al, 1987;Zimba and Grimm, 2003;Hurlburt et al, 2009) including Nile tilapia (Oreochromis niloticus) (Yamprayoon and Noomhorm, 2000;Gutierrez et al, 2011;Gutierrez et al, 2013) have been reported to be affected by offflavor problems.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake by fish occurs mainly through the gills or skin and leads to an earthy and musty smell and taste. A number of commercial important species such as Atlantic salmon, Salmo salar (Farmer et al, 1995), rainbow trout, Salmo gairdneri (From and Horlyck, 1984), catfish species (Lovell et al, 1986;Martin et al, 1987;Zimba and Grimm, 2003;Hurlburt et al, 2009) including Nile tilapia (Oreochromis niloticus) (Yamprayoon and Noomhorm, 2000;Gutierrez et al, 2011;Gutierrez et al, 2013) have been reported to be affected by offflavor problems.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations varied within individual ponds at different sampling times as well as between different ponds. Such variations in the concentration of off-flavour compounds between rearing ponds has been well documented (Lovell 1983, Lovell et al 1986, Martin et al 1988, van der Ploeg & Boyd 1991, van der Ploeg et al 1992. While GSM was undetectable in 12% of all water samples, elevated (> 0.5 µg l −1 ) GSM levels typi cally persisted for 2 to 4 wk.…”
Section: Discussionmentioning
confidence: 70%
“…In temperate localities, the production of offflavour taint is somewhat seasonal, with GSM/2-MIB production often suppressed during winter periods (Lovell et al 1986, Robertson et al 2006, Robin et al 2006. Lower temperatures and decreased solar radiation appear to be the cause, as the microbes responsible for GSM/2-MIB production experience suboptimal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The major differences in water quality were higher pH (8.57 vs 8.32 at afternoon and 8.13 vs 7.32 at dawn), total alkalinity (244. Geosmin and 2-methylisoborneol (MIB) are the most common causes of off-flavour in catfish [12,13]. These compounds are produced by species of cyanobacteria (blue-green algae) found in catfish aquaculture ponds [14].…”
Section: Resultsmentioning
confidence: 99%